2003
DOI: 10.1002/pits.10092
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy, goal orientation, and fear of failure as predictors of school engagement in high school students

Abstract: Lack of school engagement among adolescents in this country remains a problem that can have very serious consequences including increased risk for school dropout, substance use, teenage pregnancy, and criminal activity. Clearly, identification of psychological variables (selfvariables) of individuals that facilitate or hinder adolescents' levels of school engagement would contribute greatly to the understanding of how to increase adolescents' psychological well-being and their achievement motivation and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
2
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(184 citation statements)
references
References 20 publications
(25 reference statements)
7
159
2
16
Order By: Relevance
“…In addition, research with school students has shown that perfectionism is related to numerous characteristics PERFECTIONISM AND SCHOOL ENGAGEMENT 4 and processes that are closely linked to school engagement (e.g., effort invested in schoolwork, adaptive study strategies) and predictive of educational success (e.g., academic efficacy, academic achievement; Rice & Slaney, 2002; see also Stoeber, Edbrooke-Childs, & Damian, in press). In turn, school engagement has shown negative relations with fear of failure and positive relations with mastery goal orientations (e.g., Caraway, Tucker, Reinke, & Hall, 2003;Ryan & Patrick, 2001;Walker, Greene, & Mansell, 2006).…”
Section: Perfectionism and School Engagementmentioning
confidence: 99%
“…In addition, research with school students has shown that perfectionism is related to numerous characteristics PERFECTIONISM AND SCHOOL ENGAGEMENT 4 and processes that are closely linked to school engagement (e.g., effort invested in schoolwork, adaptive study strategies) and predictive of educational success (e.g., academic efficacy, academic achievement; Rice & Slaney, 2002; see also Stoeber, Edbrooke-Childs, & Damian, in press). In turn, school engagement has shown negative relations with fear of failure and positive relations with mastery goal orientations (e.g., Caraway, Tucker, Reinke, & Hall, 2003;Ryan & Patrick, 2001;Walker, Greene, & Mansell, 2006).…”
Section: Perfectionism and School Engagementmentioning
confidence: 99%
“…Engagement refers to the intensity and emotional quality of students' involvement (Connell, 1990;Fredricks, Blumenfeld, & Paris, 2004). It is a holistic construct having a behavioral (e.g., on-task behavior coupled with goal-directed activity and persistence), affective (e.g., interest, curiosity), and cognitive component (e.g., use of deep-level learning strategies) (Ainley, 1993;Blumenfeld, Megendoller, & Puro, 1992;Connell, 1990;Caraway, Tucker, Reinke, & Hall, 2003;Furrer & Skinner, 2003;Meece, Blumenfeld, & Hoyle, 1988;Skinner, Wellborn, & Connell, 1990). Engagement is a promising construct in education because it has the potential to integrate numerous bodies of literature (e.g., motivation, cognitive strategies) and provide a unified framework for studying education (Fredricks et al, 2004).…”
Section: Defining and Conceptualizing Transformative Experiencementioning
confidence: 99%
“…Specifically, it is considered the main model for understanding and predicting graduation of students from high school (Fall & Roberts, 2012). Previous studies have found that students who are careful to attend all of their classes, concentrate on learning, and obey the schools' rules and regulations, generally achieve higher grades (Caraway, Tucker, Reinke, & Hall, 2003;Wang & Holcombe, 2010). Additionally, (Finn & Rock, 1997;Moretti, 2007) pointed out that poor school engagement can increase rates of school failure, withdraw, dropout and problematic behavior.…”
Section: Introductionmentioning
confidence: 99%